The synergistic action of three piper plant extracts and biofertilizer for growth promotion and biocontrol of blast disease in red rice - Luh, Ni Suriani; Suprapta, Dewa Ngurah; Indrayani, Agung Wiwiek; Herlambang, Susila; Resiani, Ni Made Delly; AL-Shwaiman, Hind A.; Al Khulaifi, Manal M.; M. Elgorban, Abdallah; Datta, Rahul; Sri Gunawan; Tan, Ali Kee Zuan (MDPI, 2021)
Bali is a world tourist destination and has many natural resources that need to be developed to support the tourism sector. One of the local Bali resources that has the potential to be developed to support tourism and food is the local red Bali rice. This local Balinese rice is a characteristic of the ecotourism area of the Jatiluwih village of Tabanan, Bali. Balinese rice is grown with inorganic pesticides and there is an urgent need to develop organic pesticides as a sustainable approach to rice farming. In this regard, extracts of piper plants can serve as the best and greenest biopesticides as plant growth-promoting rhizobacteria (PGPR), and compost functions as organic fertilizer. The present research aimed to evaluate PGPR, compost, and the synergistic biopesticidal effects of extracts of three piper plants, namely Piper caninum, Piper betle var. Nigra, and Piper betle, against blast disease in Bali red rice plants. The results showed that the synergistic action of PGPR, compost, and crude extract of piper plant provided an inhibitory activity against blast disease in rice plants where the greatest inhibition was found in a mixture of the three extracts with an inhibition of 50 cm. This shows that the mixed compounds of the three piper extracts work synergistically in suppressing blast disease; in addition, PGPR also exhibited a positive impact on the growth of red rice because PGPR produce growth hormones and various antifungal metabolites that help the plant growth and induce systemic resistance against phytopathogens. The active principles were identified as citronella, trans-geraniol, and 4.6-dipropyl-nonan-5-one. A combination of these extracts with compost and PGPR showed potential antifungal activity against blast disease at a concentration of 2%. This application also promoted the growth of Bali red rice. There is a significant increase in the number of leaves and the number of tillers, where the height is inversely proportional to the higher the extract up to 2%, as the height of the red Bali rice plant decreases. This is good because it reduces the red Bali rice stalks’ possibility of falling during small production. The piper extract mixture at a concentration of 2% had the highest effect on grain production/tonne (6.59 tonne/ha) compared to the control at only 3.21–3.41 tonnes/ ha. The 2% concentration of the extracts from the mixture of the three pipers has the highest effect on growth and red Bali rice production, and provides the greatest obstacle to the intensity of blast disease in red Bali rice.